Monolithic solder-on nanoporous Si-Cu contacts for stretchable silicone composite sensors - Kasimatis,M; Nunez-Bajo,E; Grell,M; Cotur,Y; Barandun,G; Kim,J-S; Guder,F (ACS Applied Materials and Interfaces, 2019)
We report a method of creating solderable, mechanically robust, electrical contacts to interface (soft) silicone-based strain sensors with conventional (hard) solid-state electronics using a nanoporous Si-Cu composite. The Si-based solder-on electrical contact consists of a copper-plated nanoporous Si top surface formed through metal-assisted chemical etching and electroplating, and a smooth Si bottom surface which can be covalently bonded onto silicone-based strain sensors through plasma bonding. We investigated the mechanical and electrical properties of the contacts proposed under relevant ranges of mechanical stress for applications in physiological monitoring and rehabilitation. We also produced a series of proof-of-concept devices, including a wearable respiration monitor, leg band for exercise monitoring and Squeeze-ball for monitoring rehabilitation of patients with hand injuries or neurological disorders, to demonstrate the mechanical robustness and versatility of the technology developed, in real-world applications.